ADSORPTION OF CU2+ IONS USING FLOATING ?-CARRAGEENAN BEADS ADSORBENT - Marsyanda, Farra
The need for copper has increased in the last few centuries. Increased production activities lead to an increase in the amount of waste in the form of metal ions that accumulate in aquatic systems. The metal ion pollutant Cu2+ is soluble in water and has toxic properties even at low concentrations. This contamination can be overcome by using a floating adsorbent to facilitate the process of separating the adsorbent after it has been contacted with a polluted aquatic system. One of the commonly used adsorbent materials is carrageenan with an anionic surface of the sulfate ester group. Characteristics of floating ?-carrageenan beads prepared using CaCO3 and Na2CO3 salts as pore forming agents were investigated and compared. Determination of the composition of carrageenan to carbonate in terms of physical properties, swelling degree, float time, and adsorption capacity of Cu2+ ions by the beads. The CaCO3 salt obtained with a carbonate:carrageenan mass ratio of 1:4 gave the best character and physical properties of the beads with an adsorption capacity value of 3,41 mg/g. The characterization of the adsorbent carried out using Fourier Transformation Infra-Red (FTIR) spectroscopy showed a significant shift by the absorption of sulfate ester groups at a wavelength of around 1260 cm?1 presumably due to the formation of crosslinks by K+ ions in the ?-carrageenan beads. Optimum conditions for adsorption of Cu2+ ions by ?-carrageenan grains were obtained at pH 5, contact time of 120 minutes, and using an adsorbent mass of 0,05 gram for analyte with a concentration of 50 ppm. Based on studies of adsorption kinetics and isotherms, the maximum adsorption capacity of Cu2+ ions obtained by floating ?-carrageenan beads was 17,06 mg/g using the Langmuir adsorption isotherm model and pseudo second order adsorption kinetics. The adsorption process of Cu2+ ions by the floating ?-carrageenan grains was spontaneous and exothermic in terms of the ?G values of ?30.92 kJ.mol?1 (303 K), ?30.92 kJ.mol?1 (313 K), and ?30.93 kJ.mol?1 (323 K), and the values of ?H and ?S are ?30.77 kJ.mol?1 and 0.49 J.K?1mol?1, respectively.